GIS-Based Study on the Spatial Distribution Patterns of Public Senior High Schools in Pekanbaru City - Pahri, Aina (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This study analyzes the spatial distribution of public senior high schools in Pekanbaru City using a Geographic Information System (GIS) approach. Location data from 19 schools were collected through field surveys and analyzed using the Average Nearest Neighbour (ANN) method in ArcGIS. The analysis produced a Nearest Neighbour Ratio (NNR) of 1.44, with a significant z-score and p-value, indicating a dispersed distribution pattern. This means that schools are relatively spread across the city rather than concentrated in certain areas. Although this pattern suggests a degree of spatial balance at the city level, several districts still lack public senior high schools, showing that equitable access to upper secondary education has not been fully achieved. The findings emphasize the importance of integrating GIS and spatial analysis into education planning to support more equitable, efficient, and data-driven policies for school facility provision in growing urban areas.